Strategy for Developing a Body of Knowledge on Graduate Entrepreneurship - Sangkaew, Pimchanok; Vongkamjan, Suphawan; Chaipiboon, Somkiat (Richtmann Publishing, 2013)
The objectives were 1) to create strategy for developing a body of knowledge on graduate entrepreneurship and 2) toexperiment strategies for developing a body of knowledge on graduate entrepreneurship. Qualitative research and quantitativeresearch approaches were used. Data collection and analysis were done with In-Depth interview and focus group discussionfor qualitative research. The experiment group composed of 60 students from Kamphaeng Phet Rajabhat University Maesotand was selected with Purposive Sampling Technique. The strategic for developing a body of knowledge on graduateentrepreneurship was composed of 3 system units as the followings.1. Changing attitudes 2. Organizing activities 3.Developing a sustainability. The experimental results of the 60 students showed that their post-test attitude mean score with4.33 , was higher than their pre-test attitude mean score with 3.03. In addition, 83.33 percents of the students gained a betterunderstanding on how to write a business plan, and they were able to real practice by setting up their own. The overalloutcome of the strategy for developing a body of knowledge on graduate entrepreneurship was at good level. Those trainedstudents had increased knowledge and ability of entrepreneurship than untrained with statistical significance at 0.0001. Therewere 56 students who can use body of knowledge on graduate entrepreneurship 60 students, 93.33 percents. Moreover, theyhave applied what they have learned into their real life. These outcomes have led us to believe that the students will be able tocontinue developing and improving themselves to be well-mannered entrepreneurs.